An Observational Study on Aberrant Methylation of Runx3 With the Prognosis in Chronic Atrophic Gastritis Patients. Issue 20 (May 2016) - Zhao, Chunna; Li, Ping; Zhang, Lili; Wang, Bei; Xiao, Lili; Guo, Feng; Wei, Yueguang
Abstract : Abstract: The aim of this study is to discuss whether the methylation levels of Runx3 could be used as the early biomarker for predicting the prognosis in chronic atrophic gastritis (CAG) patients. A total of 200 subjects including 60 controls without CAG (Group 1), 70 patients with mild CAG (Group 2), and 70 patients with moderate and severe CAG (Group 3) were recruited for this cross-sectional investigation in the Department of Gastroenterology in Daqing Oilfield General Hospital from July 2013 to May 2014. The MlALDI-TOF-MS was used to measure the methylation levels of Runx3 in all of the subjects. Real-time quantitative reverse transcription polymerase chain reaction and western blotting were chosen to determine the expression levels of Runx3. The correlations between methylation levels of Runx3 among these CAG patients and their prognosis were shown by logistic regression models. The results demonstrated that the methylation levels of CpG13, CpG14, and CpG15 in Runx3 were higher in Group 3 than those in Groups 1 and 2 ( P <0.05), whereas the mRNA and protein expression levels of Runx3 were lower in Group 3 than those in Groups 1 and 2 ( P <0.05). There were significantly negative correlations between the methylation levels of Runx3 with its expression and the healing prognosis of CAG patients. In brief, this study proved that the hypermethylation modifications of CpG13, CpG14, and CpG15 in the promoter region of Runx3 could result in the down regulation of Runx3 expression to affect the prognosis of CAG. So the methylation levels of these CpG sites in Runx3 in the peripheral blood can be used as the biomarker for predicting the healing prognosis of CAG patients.